2011
DOI: 10.1124/mol.111.071282
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Structural Relevance of Conserved Positively Charged Lysine Residues in Organic Anion Transporting Polypeptide 1B3

Abstract: The human organic anion transporting polypeptide 1B3 (OATP1B3), located in the basolateral membrane of hepatocytes, mediates the uptake of endogenous substrates such as taurocholate and drugs from blood into hepatocytes. The transport activity of OATP1B3 is influenced by positively charged amino acids, which are facing the central pore. Molecular modeling was performed to select conserved positively charged amino acids, which may influence transport activity and anchoring of OATP1B3 in the plasma membrane. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 26 publications
(29 citation statements)
references
References 20 publications
1
27
0
1
Order By: Relevance
“…The latter two OATP isoforms were included to increase the quality of the alignment. From this alignment, amino acids previously shown to be important for OATP activity (Meier-Abt et al, 2005;Mandery et al, 2011) were selected and translated to a descriptor based on Z-scales or a feature-based ProtFP descriptor (Lapinsh et al, 2002;van Westen et al, 2011a). Supplemental Figure 1 shows the similarity of the proteins as described by the Z-scales descriptors in a twodimensional plot.…”
Section: In Silico Modeling For the Prediction Of Oatp1b Inhibitionmentioning
confidence: 99%
“…The latter two OATP isoforms were included to increase the quality of the alignment. From this alignment, amino acids previously shown to be important for OATP activity (Meier-Abt et al, 2005;Mandery et al, 2011) were selected and translated to a descriptor based on Z-scales or a feature-based ProtFP descriptor (Lapinsh et al, 2002;van Westen et al, 2011a). Supplemental Figure 1 shows the similarity of the proteins as described by the Z-scales descriptors in a twodimensional plot.…”
Section: In Silico Modeling For the Prediction Of Oatp1b Inhibitionmentioning
confidence: 99%
“…16 Although not directly studied at the BBB, OATP1A2 has been shown to transport rosuvastatin in isolated human hepatocytes and atorvastatin in human embryonic kidney cells (HEK293) stably transfected with OATP1A2. 17,18 Using our in vivo model of pain/inflammation, we have shown that Oatp1a4 is a BBB transporter that can be exploited to optimize CNS delivery of opioid peptide drugs; 19 however, Oatp1a4-mediated delivery of statins across the brain microvascular endothelium under conditions of H/R has not been clearly elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…All cell culture media supplements were obtained from Invitrogen GmbH (Karlsruhe, Germany). Transient expression of the prostaglandin transporter OATP2A1 in the HEK293-EP4 cells and the respective control cells was performed by using an OATP2A1 containing pcDNA3.1(+)-plasmid [3] and Lipofectamine 2000 (Invitrogen GmbH, Karlsruhe, Germany) as previously described [24,26].…”
Section: Cell Culture and Generation Of Hek293 Cell Lines Stably Exprmentioning
confidence: 99%